The Influence of EU Enlargement on EURO - Kirnos, I.O.; Lukashenko, T.M. (Економічний вісник Донбасу, 2013)
This article deals with application of model correlation-regression analysis whereby, We can evaluate the quality of the influence of certain factors which destabilize the level of euro currency. But it was stated that this does not lead to the destabilization of the overall system - Euro currency because not all systems that are not stable are unstable. Destabilization of any factors - this is a normal phenomenon, if the system is willing and able to recover. У статті розглянуто застосування моделі кореляційно-регресійного аналізу, за допомогою чого виявили тісноту і якість впливу певних факторів, дестабілізуючих рівень Євровалюти. Автори констатують, що це не призведе до дестабілізації всієї системи - Євровалюти, оскільки не всі системи, які не є стабільними, є нестійкими. Дестабілізація будьяких факторів - це нормальне явище, якщо система прагне і має можливість відновитися. В статье рассмотрено применение модели корреляционно-регрессионного анализа с помощью чего, авторы выявили тесноту и качество воздействия определенных факторов, дестабилизирующих уровень Евровалюты. Но было констатировано, что это не приведет к дестабилизации целой системы - Евровалюты, так как не все системы, которые не являются стабильными, являются неустойчивыми. Дестабилизация любых факторов - это нормальное явление, если система стремится и имеет возможность восстановиться.